Επίδραση της δραστικής ουσίας Kresoxim Methyl στη φυσιολογία φυτών μηδικής (Medicago Truncatula l.) - Κεβεζέ, Μαρία (Τμήμα Γεωπονικών Επιστημών, Βιοτεχνολογίας και Επιστήμης Τροφίμων, Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2013)
Kresoxim-methyl (KM) belongs to the group of strobilurins, one of the most important classes of agricultural fungicides, displaying a direct effect on physiological and developmental plant processes, thus leading to greening of plants via induction of hormonal biosynthesis. The aim of the present study was to examine the effect of KM pre-treatment on Medicago truncatula plants (ecotype Jemalong A17) grown under physiological conditions, evaluating key physiological, biochemical and molecular parameters. Foliar application with 10-8 M KM resulted in increased stomatal conductance and chlorophyll fluorescence in 3-day and 9-day leaves compared with control plants. The non-damaging role of KM was supported by the lack of increase in lipid peroxidation levels compared to control. However, KM pre-treatment resulted in increased of proline content, potentially marking the activation of defence mechanism to protect the plant. In point of nitric oxide (NO) and hydrogen peroxide (H2O2) were not observed any statistically significant increases. Furthermore, gene expression (AOX, GST, CAPX, FeSOD, NR, Nitrite-tr, Nitrate-tr, ADH, CAT, MIPS, P5CS, P5CR, NADde) analysis with the employment of quantitative real-time polymerase chain reaction (qRT-PCR) revealed differential regulation of all genes examined both after 3 d and 9 d, following application. KM pre-treatment under normal conditions of growth resulted in significant induction of most genes in 3-day plants, whereas a suppression of most genes was observed in 9-day plants compared to controls. Overall, the addition of KM resulted in activation of the defence mechanism of the plant, thus potentially priming the plant tolerance to stress conditions.
Keywords: Kresoxim-methyl; Strobilurins; Medicago Truncatula; Στρομπιλουρίνες